The Impact of an Android Application on Compliance With Iron Supplementations in Pregnant Women - Enny Susilawati; Yuli Suryanti; Lia Artika Sar; Ika Murtiyarini (Iran University of Medical Sciences, 2021)
Background: Monitoring the adherence of pregnant women to taking iron supplements indicates controlling the appropriateness of taking a certain number of supplements. This increases the odds of effective iron absorption; a process that occurs by consuming at least 30 iron pills a month to prevent gestational anemia. This study aimed to determine the effects of monitoring pregnant women's compliance in taking up iron supplements through an Android application in Jambi City, Indonesia. Methods: This was a quasi-experimental single group study with a pre-test-post-test design. The study subjects included 50 pregnant women in their third trimester referring to 3 maternity Hospitals in Jambi City, Indonesia, in 2020. Initial data were obtained through Hemoglobin (Hb) measurements before being given a monitoring application and subsequent Hb level checks after giving the application. The obtained data were analyzed by t-test and Mann-Whitney U test in SPSS v. 16. A significance level of 5% was considered. Results: The results obtained in the initial examination indicated that the minimum Hb level was equal to 7.3 g/dL and the maximum level was measured as 11.2 g/dL. After the intervention, the Hb level increased to a minimum of 7.6 g/dL and a maximum of 12.2 g/dL. The Mann-Whitney U test data suggested a significant difference in the degree of compliance of pregnant women with iron supplementation (P=0.010). Conclusion: Monitoring through the Android application increased pregnant women's compliance with taking iron supplements and presented a linear impact on increasing their Hb level.